Heterogeneity in the vasodilatory function of individual extremities. (February 2020) - Kadoguchi, Tomoyasu; Horiuchi, Masahiro; Kinugawa, Shintaro; Okita, Koichi
Objectives: Heterogeneity and homogeneity in the flow-mediated dilation of the human body's individual extremities are not fully understood, and the relationship between flow-mediated dilation and local muscle activity is unclear. We assessed the flow-mediated dilation of four individual extremities and sought to determine the contribution of local muscle activity (evaluated as muscle strength) to the flow-mediated dilation in each extremity. Methods: Thirteen healthy young right-handed nonactive males participated. The flow-mediated dilation in the brachial and popliteal arteries at both arms and legs was assessed by ultrasound Doppler. Muscle strength was evaluated as the grip strength and knee extension. Results: There was a significant difference in the brachial artery (BA)-FMD values between the subjects' dominant and non-dominant sides (8.0 ± 2.8 vs. 5.5 ± 2.2%, p < 0.05), whereas the two sides showed similar popliteal artery (PA)-FMD values. There was no significant correlation in flow-mediated dilation between the dominant brachial artery and popliteal artery. The BA-FMD was significantly correlated with the grip strength in both upper extremities (dominant: r = 0.562, non-dominant: r = 0.548; p < 0.05, respectively). Conclusion: These results demonstrated heterogeneity in the flow-mediated dilation of individual extremities. We observed that local muscle activity can affect the local vascular function. Measurements of vasodilatory function in individual extremities should thus be carefully considered.